Seleção de fornecedores sustentáveis utilizando Fuzzy DEMATEL-ANP - Rodrigues, Letícia Reis (Universidade Federal de São Carlos, 2017)
The issue of sustainability, which is an increasingly important consideration in the day-to-day operations of businesses, needs to be addressed in the context of supplier selection. The use of multi-criteria approaches in decisions concerning the selection of sustainable suppliers can be a valuable approach for helping to resolve the complexity of this process. A systematic review of the literature highlighted gaps in the research in this area, such as the lack of a detailed description of multi-criteria methods, as well as a scarcity of sustainability criteria that take into account the three main perspectives (Economic, Environmental, and Social). This work describes the development and real case application of a DEMATEL (Decision-Making Trial and Evaluation Laboratory) and ANP (Analytic Network Process) fuzzy modeling technique for the selection of sustainable suppliers. The methodological approach used in the research was quantitative, descriptive, and empirical. The modeling and simulations were performed using MATLAB®. Incorporation of the specificities of the process of selection of sustainable suppliers makes the model a useful tool for use by both businesses and researchers concerned with the issue of sustainability. A systematic review of the published research highlights the main state-of-art methods and criteria used for the selection of green and sustainable suppliers. The model is described in a framework highlighting each step of the application. It was subsequently applied by a major glass packaging company, where the supply chain coordinator agreed to assist in the research. The outputs of the second phase of the model showed that the Economic cluster was most important and interacted with the Environmental cluster, while the Social cluster remained practically inert, without interactions with the other clusters. For the three perspectives, the three most influential criteria were as follows: cost, compliance, and quality (Economic perspective); environmental certifications/ISO 14001, reuse/recovery, and pollution control (Environmental perspective); and stakeholder rights, respect for policies, and encouragement of the development of self-sustainable recycling programs (Social perspective). Finally, a supplier was selected using the framework presented, and the criteria that most influenced the decision were highlighted. The procedure developed here offers a tool to assist businesses searching for sustainable solutions, as well as researchers in the scientific community concerned with the development of knowledge in this area.
Sustainable supplier selection using Fuzzy DEMATEL-ANP
Keywords: Seleção de fornecedores; Sustentabilidade; Seleção de fornecedores sustentáveis; Fuzzy; Selection of suppliers; Sustainability; Selection of sustainable suppliers; ENGENHARIAS::ENGENHARIA DE PRODUCAO